Characteristics of Continuing Current Waveforms and M‐Component Parameters in Triggered Lightning. Issue 23 (1st December 2022) - Cai, Li; Hu, Qiang; Zhou, Mi; Tian, Ruixin; Su, Rui; Fan, Yadong; Wang, Jianguo
Abstract: Based on directly measured triggered lightning currents, the characteristics of 70 continuing current (CC) waveforms and 106 M ‐component waveforms were analyzed. The durations of CC without M ‐component are all less than 10 ms, which are significantly less than those of CCs with M ‐components. The first M ‐component always appears at no more than 4 ms after the return stroke. The characteristics of the superimposed M ‐components will be different for CC of different durations. The M ‐components superimposed on CCs with duration greater than 10 ms are 3–4 times larger in terms of risetime, half‐peak width, duration, and transfer charge than that superimposed on CCs with duration less than 10 ms. The time difference ( T D ) between the peak electric field and the peak current of the M ‐component is affected by both the continuing current level ( I CC ) and the magnitude of the M ‐component ( I M ). T D and I CC (or I M ) will not be large at the same time. The duration of a CC following a return stroke with a peak current greater than 21.2 kA will not exceed 46.0 ms. Key Points: The characteristics of continuing current and M ‐component current waveforms from triggered lightning were analyzed The characteristics of the M ‐components superimposed on continuing currents with different durations are different The time difference between the peak electric field and the peak current of the M ‐component is related to two current parameters